Fabrication and characterization of high-performance forward-osmosis membrane by introducing manganese oxide incited graphene quantum dots. (1st March 2022) - Jain, Harshita; Kumar, Ajay; Rajput, Vishnu D.; Minkina, Tatiana; Verma, Anoop Kumar; Wadhwa, Shikha; Dhupper, Renu; Chandra Garg, Manoj; Joshi, Himanshu
Abstract: Forward osmosis (FO) is the futuristic membrane desalination technology as it transcends the disadvantages of other pressure-driven techniques. But, there still remain critical challenges like fabrication of highly permeable membrane with ideal structures maintaining high rejection rates that need to be addressed for implementation as a practical technology. In this work, novel thin-film composite (TFC) membranes were fabricated by means of incorporating manganese oxide (MnO2 ) incited graphene quantum dots (GQDs) nanocomposite into a cellulose acetate (CA) suspension followed by phase inversion (PI) for enhanced FO performance. The surface morphology and chemical structure of fabricated membranes were studied using various characterization techniques like XRD, FT-IR, SEM-EDS, Mapping, AFM, and TGA. The structural parameters, water flux, reverse salt flux and salt rejection was estimated on the basis of data obtained from four varying initial draw solution concentrations. At high nanocomposites stacking, the hydrophilicity of the casting blend increase, and subsequently, the PI exchange rate additionally increases, which brings about noticeable difference in the surface morphology. The membrane with 0.5 wt% nanocomposite exhibited superior FO separation performance with osmotic water flux of 18.89, 34.49, 41.76 and 42.34 in L.m −2 .h −1 with variable concentrations of NaCl salt solution (0.25M, 0.5M, 1M, and 2M), respectively. Also, the porosity of the membrane was increased to 47.23% with 96.87% salt rejection. The results indicate that the hydrophilicity of the nanocomposite drives them to the interface among CA and water during PI process leading to solid hydrogen bonding to achieve high water permeability. Graphical abstract: Image 1 Highlights: FO membranes with GQDs-MnO2 nanocomposite are prepared targeting improved separation performance. Solid H-bonding among nanocomposite and CA is upheld by expanded consistency of the casting solution. Hydrophilicity of the nanocomposite drives them to the interface among CA and water. The prepared membranes show brilliant pure water flux, reverse salt flux and high salt rejection.